Decline Curve Analysis of Shale Oil Production Using a Constrained Monte Carlo Technique - Fanchi, John R. (Journal of Basic & Applied Sciences, 2020)
Shale oil production from the Bakken shale and the Eagle Ford shale was analyzed using decline curve analysis and a constrained Monte Carlo technique. The purpose of the paper is to provide a set of parameters that can be used to initialize a Monte Carlo analysis of shale oil production using a selection of decline curves. The parametersare obtained by matching shale oil production for a set of wells in the Eagle Ford shale and the Bakken shale.